DFT and experimental studies on Rh(III)-catalyzed dual directing-groups-assisted [3+2] annulation and ring-opening of N‑aryloxyacetamides with 1-(phenylethynyl)cycloalkanol. (13th April 2021) - Zhou, Jia; Li, Zi-Hao; Pan, Jin-Long; Chen, Chao; Ma, Xue-Feng; He, Yuhan; Ding, Tong-Mei; Zhang, Shu-Yu
Graphical abstract: Highlights: Two different pathways have been ascertained to different products with DFT. The ring-opening or not in different cycloalkanols depended on their ring members. 4-membered ring was the critical structure for high ring strain and steric hindrance. Abstract: A density functional theory (DFT) has been conducted to elucidate the mechanism of N-aryloxyacetamides reacting with 1-(phenylethynyl)cyclobutanol and 1-(phenylethynyl)cyclopentanol under rhodium (III) catalysis. The impact of substrates with different ring numbers on the reaction mechanism has been discussed in detail. When the ring number exceeds 4, 1-(phenylethynyl)cycloalkanol simply conducts [3+2] annulation like the general reaction between N -aryloxyacetamides and alkyne. When the ring number is equal to 4, 1-(phenylethynyl)cyclobutanol undergoes cascade [3+2] annulation and ring-opening reaction via rhodium (III) catalysis. The results show that the ring-opening or not in 1-(phenylethynyl)cycloalkanol depends on ring members and the 4-membered ring is the critical structure for its high ring strain and steric hindrance.